A longitudinal study of twins from birth to adulthood - Anne Mari Korbøl Torgersen (Norsk Forening for Epidemiologi, 2016)
Temperamental variation in infancy was the starting point for this longitudinal study of twins followed from birth to adulthood. The influence of early individuality on later development was a research question in the follow-ups, and by choosing twins as a group, it was possible to uncover the effect of environmental and genetic factors at the different ages. Developmental psychopathology turned out to be a relevant framework, where mental health and well-being are seen as the result of a continuous transaction between geneticallybased individuality and a changing and varying environment (Maughan & Rutter, 2008). The twin method was an adequate tool to gain a better understanding of these processes. The overall clear message from the study is that whereas heritability of temperament can be seen from infancy on, environmental factors are of crucial importance for an understanding of mental development and health, but the effect of environmental factors probably varies a great deal in dependency upon the genetic disposition of the person.